Analysis of the risk of early postoperative complications after Bentall procedure - V.A. Tymoshenko; B.M. Todurov (Кардіохірургія та інтервенційна кардіологія)
The aim – to investigate the frequency of early postoperative complications and to analyze possible predictors of the prolonged stay of patients in the intensive care unit (ICU) after Bentall procedure. Materials and methods. In the study, the medical histories of adult patients (from 18 to 75 years old) who underwent Bentall procedure for ascending aortic aneurysm at the State Institution «Heart Institute of the Ministry of Health of Ukraine» between 2012 and 2021 were analyzed. Univariate and multivariate analysis (logistic regression) was used to determine prognostic risk factors. Results. Patients with prolonged stay in intensive care unit were characterized by significantly older age (p = 0.005), more frequent presence of comorbidities of arterial hypertension (p = 0.044) and significantly lower initial values of glomerular filtration rate (p = 0.045). In addition, these patients were 3.6 times more likely (p = 0.0005) to use an autohemotransfusion device and almost 6 times more likely (p = 0.0037) to require rethoracotomy due to bleeding. Acute renal failure was recorded 4.3 times (p = 0.0002) and acute respiratory failure was recorded 3.3 times more often (p = 0.0004). The duration of mechanical ventilation (OR 1.204 (CI 1.053–1.377), p = 0.007) and the development of acute renal failure (OR 4.069 (CI 1.040–15.923), p = 0.044) were two independent predictors of prolonged stay of patients in ICU. Conclusions. For patients with risk factors for a prolonged ICU stay after surgery, more active treatment strategies before and after surgery are recommended to avoid possible complications and shorten hospital stay.